2010
DOI: 10.1084/jem.20092506
|View full text |Cite
|
Sign up to set email alerts
|

Cancer-associated metabolite 2-hydroxyglutarate accumulates in acute myelogenous leukemia with isocitrate dehydrogenase 1 and 2 mutations

Abstract: Mutations in isocitrate dehydrogenase 1 and 2 (IDH1/2), are present in most gliomas and secondary glioblastomas, but are rare in other neoplasms. IDH1/2 mutations are heterozygous, and affect a single arginine residue. Recently, IDH1 mutations were identified in 8% of acute myelogenous leukemia (AML) patients. A glioma study revealed that IDH1 mutations cause a gain-of-function, resulting in the production and accumulation of 2-hydroxyglutarate (2-HG). Genotyping of 145 AML biopsies identified 11 IDH1 R132 mut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
616
1
8

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 668 publications
(642 citation statements)
references
References 25 publications
17
616
1
8
Order By: Relevance
“…4 However, recent studies showed that impaired platelet production also contributes to the pathogenesis of ITP. 5 Consistent with these findings, two second-line thrombopoietin receptor (TPO-R) agonists, romiplostim (Nplate, Amgen, Thousand Oaks, CA, USA) and eltrombopag (Promacta, GlaxoSmithKline, Research Triangle Park, NC USA), 6 showed remarkable efficacy in patients with primary ITP. 7,8 As these trials excluded patients with secondary ITP, the activity of these new drugs in CLL-associated ITP has not been reported.…”
Section: Conflict Of Interestmentioning
confidence: 73%
See 1 more Smart Citation
“…4 However, recent studies showed that impaired platelet production also contributes to the pathogenesis of ITP. 5 Consistent with these findings, two second-line thrombopoietin receptor (TPO-R) agonists, romiplostim (Nplate, Amgen, Thousand Oaks, CA, USA) and eltrombopag (Promacta, GlaxoSmithKline, Research Triangle Park, NC USA), 6 showed remarkable efficacy in patients with primary ITP. 7,8 As these trials excluded patients with secondary ITP, the activity of these new drugs in CLL-associated ITP has not been reported.…”
Section: Conflict Of Interestmentioning
confidence: 73%
“…6,7 Arginine substitutions in both IDH1 and IDH2 are likely gain-of-function mutations that would result in the accumulation of 2-hydroxyglutarate. 6 We identified one case of refractory anemia with ringed sideroblast and thrombocytosis harboring a JAK2 V617F mutation together with an IDH2 R140L substitution. IDH2 mutations have been shown to be acquired during the evolution of two cases of JAK2 V617F-positive MPN to AML.…”
mentioning
confidence: 99%
“…Recurrent somatic point mutations in active site arginine residues of IDH1 (R132) and IDH2 (R140 and R172) have been found in multiple tumors, including acute myeloid leukemia (AML; refs. [3][4][5][6][7][8][9]. Cancer-associated IDH1/2 mutations confer the neomorphic activity of reducing αKG to the oncometabolite (R)-2-hydroxyglutarate (2HG; refs.…”
Section: Introductionmentioning
confidence: 99%
“…10,11 The IDH mutants gain the neomorphic enzyme activity and lead to the production of an onco-metabolite, 2-hydroxyglutarate (2-HG), which was speculated to upregulate hypoxia-inducing factor 1a by inhibition of prolyl hydroxylase. 1,2,10,12 On the basis of the in vivo functions of IDH1 and IDH2, it is intuitive to expect similar clinical and biological characteristics between AML bearing mutations of these two genes. Indeed, mutations of both genes are more commonly present in patients with normal cytogenetics.…”
Section: Introductionmentioning
confidence: 99%